Continental-Scale Gene Flow Prevents Allopatric Divergence of Pelagic Freshwater Bacteria. (2nd February 2021) - Hoetzinger, Matthias; Pitt, Alexandra; Huemer, Andrea; Hahn, Martin W
Abstract: Allopatric divergence is one of the principal mechanisms for speciation of macro-organisms. Microbes by comparison are assumed to disperse more freely and to be less limited by dispersal barriers. However, thermophilic prokaryotes restricted to geothermal springs have shown clear signals of geographic isolation, but robust studies on this topic for microbes with less strict habitat requirements are scarce. Furthermore, it has only recently been recognized that homologous recombination among conspecific individuals provides species coherence in a wide range of prokaryotes. Recombination barriers thus may define prokaryotic species boundaries, yet, the extent to which geographic distance between populations gives rise to such barriers is an open question. Here, we investigated gene flow and population structure in a widespread species of pelagic freshwater bacteria, Polynucleobacter paneuropaeus . Through comparative genomics of 113 conspecific strains isolated from freshwater lakes and ponds located across a North–South range of more than 3, 000 km, we were able to reconstruct past gene flow events. The species turned out to be highly recombinogenic as indicated by significant signs of gene transfer and extensive genome mosaicism. Although genomic differences increased with spatial distance on a regional scale (<170 km), such correlations were mostly absent on larger scales up to 3, 400 km. We conclude that allopatric divergence in European P. paneuropaeus is minor, and that effective gene flow across the sampled geographic range in combination with a high recombination efficacy maintains species coherence.